2008
DOI: 10.2320/matertrans.mf200805
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Bonding Mechanism Using Silver Metallo-Organic Nanoparticles to Bulk Metals and Observation of Sintering Behavior

Abstract: We have proposed a novel bonding process using silver nanoparticles, which can be alternative to lead-rich high melting point solders. The bonding mechanism of silver metallo-organic nanoparticles to bulk materials (gold and copper) is discussed based on the observations of the bonded interface using Transmission Electron Microscope (TEM). At the interface of sintered silver and bulk gold, the crystal orientation of silver corresponded to that of gold. It is thought that the epitaxial layer of silver formed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(76 citation statements)
references
References 5 publications
4
71
1
Order By: Relevance
“…7(e). Given that fact, we consider that we achieved an effect similar to the nanoparticle bonding previously reported [6][7][8]10,11) by forming the nanoparticles during the reduction of silver oxide. Figure 10 shows TEM images of the interface between the plating film and the silver sintering layer of each of the specimens observed in Fig.…”
Section: Bond-strength Evaluationmentioning
confidence: 84%
“…7(e). Given that fact, we consider that we achieved an effect similar to the nanoparticle bonding previously reported [6][7][8]10,11) by forming the nanoparticles during the reduction of silver oxide. Figure 10 shows TEM images of the interface between the plating film and the silver sintering layer of each of the specimens observed in Fig.…”
Section: Bond-strength Evaluationmentioning
confidence: 84%
“…20) The simulated temperature was set to 523 K for comparison with our experimental result. 13) The cross section of a typical model of a silver nanoparticle and a gold substrate is shown in Fig. 2.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…We have previously observed the silver/gold interface bonded at 523 K under a bonding pressure of 5 MPa using metallo-organic nanoparticles 13) and identified that the sintered silver atoms were crystallographically oriented to the gold substrate, as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sintering behavior of metallic nanoparticles has been exploited to write electronic circuits and join components to substrate [15][16][17][18][19][20]. For example, Ide et al [16] reported achieving Cu-to-Cu joining using Ag metallo-organic nanoparticles at a low bonding temperature (573 K) and a bonding pressure of 1 or 5 MPa; the shear strength of the resulting joints was 25-40 MPa.…”
Section: Introductionmentioning
confidence: 99%